Multiple Indexing Relativism about Predicates of Taste - Dan Zeman (Crítica)
Focusing on predicates of taste, this paper puts forward a novel version of relativism, motivated by a recently discussed phenomenon: perspectival plurality. After showing that the phenomenon is problematic for at least some versions of relativism and discussing several possible answers on behalf of the relativist, I put forward my own version. The main feature of the proposal is the introduction in the index not of a single parameter for perspectives, but of a (possibly infinite) sequence of such parameters. In the last part of the paper, I defend the view against three objections.